Contaminants in commercial homoeopathic medicines - Zacharias, Carlos Renato (British Homeopathic Journal, 1995)
2 sets of homoeopathic medicines prepared from Lycopodium clavatum (6cH, 12cH and 100cH) and the dynamized water and ethanol mixture used (3cH and 6cH) were analysed using ultraviolet spectroscopy. The spectra for each set of Lycopodium and dynamized solvent were similar and differed from that of the inert solvent. The 2 sets of dynamized medicines nevertheless showed significant differences. These results suggest the possible introduction of contaminants during the dynamization process, the effects of which on clinical results are considered.
Keywords: Physics; Spectroscopy; Lycopodium clavatum; Contaminants